Scandium-catalyzed stereoselective block and alternating copolymerization of diphenylphosphinostyrenes and isoprene. Issue 23 (26th May 2022) - Fu, Tingting; Jiang, Lei; Sun, Hanyang; Hou, Zhaomin; Guo, Fang
Abstract : The coordination copolymerization of polar diphenylphosphinostyrenes and isoprene by (C5 Me4 SiMe3 )Sc(CH2 C6 H4 NMe2 - o )2 afforded a new series of phosphine-functionalized alternating and block isoprene–styrene copolymers. Abstract : The coordination copolymerization of polar diphenylphosphinostyrenes (StPPh2 ) and isoprene (IP) by a half-sandwich scandium catalyst (C5 Me4 SiMe3 )Sc(CH2 C6 H4 NMe2 - o )2 afforded a new series of phosphine-functionalized alternating and block isoprene–styrene copolymers. In the copolymerization of p -StPPh2 with IP, the incorporation of p -StPPh2 into the polymer chains started after IP was almost completely consumed, yielding the p -StPPh2 –IP diblock copolymers containing a syndiotactic-rich poly( p -StPPh2 ) block and a poly(IP) block containing 1, 4- and 3, 4-structures, probably because the coordination of IP to the catalyst is favored over that of p -StPPh2 . In the copolymerization of o -StPPh2 with IP, the o -StPPh2 –IP alternating copolymer was exclusively formed with the coexistence of the two monomers, because the successive insertion of o -StPPh2 was difficult due to steric hindrance caused by the phosphine/styrene chelation to the catalyst metal center. When an excess amount of IP was used in the copolymerization of o -StPPh2 and IP, the formation of a poly(IP) block was achieved after o -StPPh2 was consumed in the alternating copolymerization, thus affording block copolymers containing an o -StPPh2 –IP alternating block and a poly(IP) block. Moreover, the incorporation of IP in the alternating copolymerization with o -StPPh2 took place in a regio- and stereospecific cis -1, 4-fashion (95%), suggesting that the coordination (chelation) of o -StPPh2 to the catalyst could influence the regio- and stereoselectivity of IP polymerization.